Analisis Risiko Kadar Enzim SGOT dan SGPT pada Penderita Diabetes Mellitus Tipe 2 - Mochamad Rizal Maulana; Sutji Kuswarini (Poltekkes Kemenkes Semarang, 2022)
Diabetes mellitus is a group of metabolic diseases that occur due to abnormalities in insulin secretion and/or insulin action. In type 2 diabetes mellitus there is a decrease in glucose absorption by the body due to insulin resistance. Energy metabolism from glucose is processed through the synthesis of fatty acids in the liver (cytosol). The process that occurs continuously causes the accumulation of lipids in the liver or